THE SMOOTHING POTENTIAL OF DEPRECIATION FOR LOCAL AUTHORITIES - Pilcher, Robyn (The journal of contemporary issues in business and government, 2006)
The purpose of this paper is to consider the question: Does depreciation allocation provide a vehicle for local councils to smooth, maximise or minimise reported operating result? In 1968 Copeland claimed there were five properties an accounting practice must possess before it may be used as a manipulative device. These criteria have been considered with respect to depreciation expense reported by local government councils. Results confirmed the existence of unexplained ’anomalies’ which significantly impacted on a council’s operating result and subsequent performance measures used for decision-making. These, in turn, satisfied Copeland’s five manipulative characteristics. This research provides the first (known), longitudinal empirical analysis related to the charging of depreciation to transport infrastructure by local authorities. It also adds to the ’manipulation’ literature by considering its applicability in a public sector context. Future research will apply a statistical activity cost theory framework or similar instrument to ratify the findings reported here.